Cutaneous amyloidosis at the site of insulin injection with coexistence of acanthosis nigricans - Bevinahalli N Nandeesh; T Rajalakshmi; B Shubha (Wolters Kluwer Medknow Publications, 2014)
Skin is one of the important organs affected by amyloidosis which is characterized by extracellular deposition of fibrillary proteins having homogenous, eosinophilic on routine staining with distinct tinctorial properties. Nodular cutaneous amyloidosis is rare and may affect dermis, subcutis and also vascular walls. Nodular amyloid deposits in the deeper dermis occurring at the site of insulin injection are a rare observation, which is described here. This description indicates that cutaneous amyloidosis may be associated with local subcutaneous injections of insulin and may clinically mimic a neoplasm or lipodystrophic lesion.